A SOFTWARE SOLUTION FOR QUALITY ASSESSMENT OF BUSINESS PROCESS MODELS (Computer systems and information technologies, 2022)
One of the primary tools of the BPM (Business Process Management) paradigm is business process modeling. Business scenarios can be presented in the form of graphical models that can be easily understood by both Information Technology (IT) professionals and non-IT professionals – business analysts, software customers, department heads, top managers, and other stakeholders interested in business process improvement – using business process modeling. Small and large businesses can capture their operations in the form of graphic diagrams using business process modeling as the fundamental tool of the BPM approach, which can then be brainstormed by business analysts to uncover ways to optimize organizational workflows. Typically, business process improvement is accomplished by the automation of operations that have been recognized as “bottlenecks” following analysis. However, analyzing a business process model is only viable if it is clear and correct in terms of compliance with both the notation used and the actual business process it reflects. Therefore, this work examines the structural measures of the BPMN (Business Process Model and Notation) business process model. It is assumed that business process models that violate business process modeling rules are neither understandable nor suitable for further work with them, which can also lead to various errors occurring during the stage of business process analysis, as well as the stage of its improvement and implementation of proposed changes, i.e., during development, testing, and maintenance of distinct software components, information system modules, and so on. The object of this work is a process of quality assessment of business process models created using the BPMN notation. The subject of this work is a software solution for the quality assessment of business process models. The goal of this work is the evaluation of a probability of errors in business process models to improve their quality.
Keywords: software solution; quality assessment; business process model; BPMN notation